Black Womanhood in the Digital Age : Persuasive Discourse Analysis - Martial Dogou (International Journal of Social Sciences: Current and Future Research Trends, 2023)
This paper sheds light on the digital media landscape where black female media citizens engage in a deeply affective form of “information play” that replicates the enduring practices of testifying and witnessing. In the process of the information play, the audience or witness is just as important as the performer. As I explain, “however passive their role may seem,” those who bear witness to some performance of self are critical to affirming the reality that the testifier seeks to construct through their performance [9]. Thus the confirmation that black women receive from presenting their versions of black womanhood to a community of witnesses is invaluable to their interior sense of self. When their voices are heard and their conceptions of black womanhood are witnessed, black women get the affirmation required to continue performing black womanhood on their own terms